A tecnologia e o saber: discursos e representações do intelectual na internet - Silva, Maurício Júnior Rodrigues da (2010)
This research aims at investigating the discursive dimensions that the intellectuality presents in the contemporaneity. This purpose arose due to the observation that the intellectualized knowledge and culture are becoming more important in a primarily contemporary field: the internet. In such a place of discourse, it opens as a perspective for analyzing multiple dimensions attached to the intellectual discourse. From there, we can notice different practices of discourse from paths of the electronic network, which engender different perspectives of representation and identity. Due to this conclusion, we attempt to assert the sense about the effects of such practices acquired in the production of identities and representations about the intelligentsia. It was chosen as a corpus of this work e-texts, images and videos from two sites: Casa do Saber and CPFL Cultura. The first one is a center of discussion and dissemination of knowledge in São Paulo [and Rio de Janeiro], which offers access to the culture, [and intellectual knowledge in general]." The second one refers to a virtual space dedicated to publicize meetings, lectures and cultural activities in general that the CPFL Energia promotes, publishes or sponsors. For theoretical and methodological approaches, this work has its benchmark in french Discourse Analysis derived from Pêcheux and Foucault, especially in terms of considering the knowledge and power as inherent and interrelated areas. In terms of methodology, we attempted to collect text and images of the sites in question and submit them to the theoretical framework described. By bringing this perspective to the world of Web 2.0, it is possible to approach the discourse and power relations, which are essential elements in producing a subject that consists mostly of speeches. Therefore, one may ask what are the discursive strategies that those sites present, and how they are related to production of representative practices pertaining to the intelligentsia.